Study of the diagnostic significance of telomere length in patients with cerebral atherosclerosis - Yehorova, M. S.; Krasnienkov, D. S.; Hurianov, V. H.; Kondratiuk, V. Ye. (Zaporozhye Medical Journal, 2020)
Cerebrovascular diseases are one of the most important causes of morbidity and mortality in the adult population. Objective – to determine the relationship between telomere length and lipid spectrum, structural and functional state of the heart and cerebral vessels and heart rate variability in patients with 1–3 degree cerebral atherosclerosis (CA). Materials and methods. In a comprehensive clinical and instrumental study, 161 patients with 1–3 degree CA were enrolled. Telomerase activity was determined using a real-time tandem repeat amplification protocol. The relative lengths of telomeres were measured by multiplex quantitative polymerase chain reaction in real time. Results. Patients were divided into 2 groups: І – with CA of 1–2 degree, ІІ – with CA of 3 degree (who had suffered an ischemic atherothrombotic stroke (AS)). Mean age was 65.1 ± 10.5 and 65.4 ± 9.1 years, respectively. The proportion of men was 21.2 % in group I and 52 % in group II. To identify the factors that influence telomere size as a marker of early aging, the method of constructing logistic regression models was used. In building the models, the following categories were used: shorter telomere length – T/S <2.61 (low and medium tertiles); longer telomere length – T/S over 2.61. For a set of significant risk factors selection, the method of step-by-step inclusion / exclusion of signs was used (stepwise exclusion threshold value of P > 0.15 and inclusion threshold value of P < 0.03). A multivariate logistic regression model was developed based on the identified significant risk factors. A statistically significant positive relationship was found between the telomere length and both the E/A index (diastolic function of the heart) and LPVLD, as well as negative relationship with both the EF and the intima-media complex (IMC) on the right. Conclusions. Telomere length is comparable in elderly patients with 1–2 degree CA and those who suffered an ischemic atherothrombotic stroke. Based on the multifactor regression analysis, the relationship between telomere length and LPVLD, IMC, EF and LV diastolic function was detected in patients at different stages of CA, including type 2 diabetes (AUC = 0.79 (CI 0.69–0.87)).